COMPARATIVE ANALYSIS OF ARTERIAL HYPERTENSION TREATMENT IN MEN AND WOMEN BASED ON THE RESULTS OF ACCORD STUDY (ACRIDILOLE IN COMBINATION THERAPY IN PATIENTS WITH ARTERIAL HYPERTENSION AND OBESITY OR TYPE 2 DIABETES) - S. A. Shalnova; S. Yu. Martsevich; A. D. Deev; Yu. V. Lukina; E. N. Hoseva (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To compare the efficacy and safety of carvedilol in men and women with mild to moderate arterial hypertension, associated with obesity and/or compensated diabetes type 2. Material and methods. Hypertensive patients (n=592, 176 men and 416 women) with obesity and/or diabetes were involved into randomized comparative open-label study in parallel groups. Patients were randomized into two groups. Patients of group A (n=291: 90 men and 201 women) kept on to receive previous antihypertensive drugs except beta-blockers which were withdrawn and replaced with carvedilol (Acridilole®, PLC “Akrikhin”, Russia). Patients of control group (n=301: 86 men and 215 women) kept on to receive only previous antihypertensive drugs. Efficacy of antihypertensive therapy was assessed at every 2-week visits during 24-week observation. Biochemical parameters of glucose and lipid metabolism, 12-lead ECG were evaluated at baseline and at the end of the study. Target blood pressure (BP) achievement and safety was assessed in 24 weeks of treatment. Results. Women had more severe metabolic abnormalities compared with men. By the 24th week of treatment significant reduction in systolic BP , diastolic BP , and heart rate was found in the both groups of patients regardless of gender , intergroup differences were significant (p<0,05). By the end of the study target BP level was achieved in 96.3% of men and 96,8% of women in group A and 85.9% and 88.8%, respectively , in the control group (p<0,001). The number of hospital admissions decreased in 4.8 times in men (p<0.0001) and 12 times - in women (p<0.05) in group A, and in 2.7 and 3.3 times, respectively , — in the control group (p<0.0001). Mild to moderate side effects were observed in 32 patients: 19 and 13 patients in group A and control group, respectively (p=0.58). Adverse event rate was not distinguished significantly between men and women. Conclusion: The results show comparable high efficacy and safety of carvedilol in hypertensive men and women with concomitant diseases and high metabolic and cardiovascular risk.